Optimierung des Verhandlungsgebots auf dem Telekommunikationsmarkt - Vitali Gretschko; Axel Ockenfels; Achim Wambach (Wirtschaftsdienst, 2024)
The Federal Network Agency plans to extend the frequency usage rights of the established mobile network operators until 2030, combined with a negotiation requirement for 1&1's access to frequencies below 1 GHz. This analysis identifies key weaknesses of the negotiation bid: lack of clarity regarding regulatory intervention in the event of a non-agreement, inefficient last-minute effects, asymmetric negotiating power and problems with the disclosure of sensitive information. As an alternative, a structured auction procedure is proposed that includes product definition by 1&1, an explicit maximum price and a "descending clock auction" to enable a more efficient and transparent award process.
Keywords: D44; D47; L96; 330